The recourse to the Dicastery of the Clergy - Leszczyński, Grzegorz (Prawo Kanoniczne, 2024)
The 1983 Code of Canon Law, when regulating the provisions regarding hierarchical recourse, does not apply only to the Congregation of the Roman Curia, but to every hierarchically higher administrative body. The author's subject of interest is recourse to the Dicastery of the Clergy in the event that the bishop of the diocese or his delegate issues an extrajudicial decree imposing a penalty for an offense under can. 1395 CCP. According to can. 1737 § 1 of the Code of Civil Procedure, anyone who feels aggrieved by an administrative act has the right to file a recourse to the hierarchical superior of the author of the administrative act. Therefore, the article discusses the issues of the motive, object, subject of the recourse, and especially the procedure for entering the Dicastery of the Clergy.